Implementation of NTB Regional Regulation Number 5 of 2021 concerning Prevention of Child Marriage in Lendang Nangka Utara Village, Masbagik District, East Lombok Regency - Darmini, Darmini; Rizqi, Intan Purnami (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Child marriage is often considered normal by society. In fact, there are many risks or negative impacts that can arise as a result of child marriage. The increase in divorce and even domestic violence, both physical and psychological, is also one of the impacts of child marriage. The problem formulation in this thesis is how to implement NTB Regional Regulation No. 5 of 2021 concerning the Prevention of Child Marriage in North Lendang Nangka Village, Masbagik District, East Lombok Regency and what factors influence this implementation. The type of research used by the author is qualitative research, with research analysis including three stages, namely: data reduction, data presentation and drawing conclusions. This research method uses data collection techniques, namely: observation, interviews and documentation. The results of the research show that Lendang Nangka Utara village has implemented NTB Regional Regulation No. 5 of 2021 concerning Prevention of Child Marriage. In fact, the implementation of this regional regulation was able to have an impact on reducing the number of child marriages in Lendang Nangka Utara village. Form of implementation of NTB Regional Regulation No. 5 of 2021 concerning the Prevention of Child Marriage in Lendang Nangka Utara village includes: establishing Village Regulations, conducting outreach and forming a special youth forum. The factors that cause the NTB Regional Regulation to be implemented well are good cooperation with all parties and high public legal awareness.